Collapse into now [compact disc] (Warner Bros., 2011)
From the veteran Alt-Rock band, REM's "Collapse Into Now" features some very special guests: Patti Smith, guitarist Lenny Kaye, Peaches, Eddie Vedder, and The Hidden Camera's frontman Joel Gibb.